ETHNOGENETIC CONCEPT OF PROFESSOR G.S. FEDOROV-GUSEYNOV (to the 80th anniversary of Gadzhi Saidovich Fedorov-Huseynov (1937-2008)) - Ibragimov, M -RA (History, Archeology and Ethnography of the Caucasus, 2017)
null